Shared ancestral susceptibility to colorectal cancer and other nutrition related diseases - Huhn Stefanie; Bevier Melanie; Rudolph Anja; Pardini Barbara; Naccarati Alessio; Hein Rebecca; Hoffmeister Michael; Vodickova Ludmila; Novotny Jan; Brenner Hermann; Chang-Claude Jenny; Hemminki Kari; et al. (BMC, 2012)
Abstract Background The majority of non-syndromic colorectal cancers (CRCs) can be described as a complex disease. A two-stage case-control study on CRC susceptibility was conducted to assess the influence of the ancestral alleles in the polymorphisms previously associated with nutrition-related complex diseases. Methods In stage I, 28 single nucleotide polymorphisms (SNPs) were genotyped in a hospital-based Czech population (1025 CRC cases, 787 controls) using an allele-specific PCR-based genotyping system (KASPar®). In stage II, replication was carried out for the five SNPs with the lowest p values. The replication set consisted of 1798 CRC cases and 1810 controls from a population-based German study (DACHS). Odds ratios (ORs) and 95% confidence intervals (CIs) for associations between genotypes and CRC risk were estimated using logistic regression. To identify signatures of selection, Fay-Wu's H and Integrated Haplotype Score (iHS) were estimated. Results In the Czech population, carriers of the ancestral alleles of AGT rs699 and CYP3A7 rs10211 showed an increased risk of CRC (OR 1.26 and 1.38, respectively; two-sided p≤0.05), whereas carriers of the ancestral allele of ENPP1 rs1044498 had a decreased risk (OR 0.79; p≤0.05). For rs1044498, the strongest association was detected in the Czech male subpopulation (OR 0.61; p=0.0015). The associations were not replicated in the German population. Signatures of selection were found for all three analyzed genes. Conclusions Our study showed evidence of association for the ancestral alleles of polymorphisms in AGT and CYP3A7 and for the derived allele of a polymorphism in ENPP1 with an increased risk of CRC in Czechs, but not in Germans. The ancestral alleles of these SNPs have previously been associated with nutrition-related diseases hypertension (AGT and CYP3A7) and insulin resistance (ENPP1). Future studies may shed light on the complex genetic and environmental interactions between different types of nutrition-related diseases.